Tracking the Effectiveness of Antibiotic Therapy using the Drug Resistance Profile of Uropathogens in Pregnant Women - Ashraf, Asfa; Iqbal, Muhammad Naeem (PSM Biological Research, 2020)
The extensive structural and functional changes in the urinary tract during pregnancy increase the risk of Urinary tract infection. UTI in pregnancy, including asymptomatic bacteriuria, is associated with maternal morbidity and adverse pregnancy outcomes such as pyelonephritis, hypertensive disease of pregnancy, anaemia, chronic renal failure, premature delivery, and foetal mortality. The effective appropriate antimicrobial agent is a major concern as many effective antimicrobial groups cannot be used due to their potential toxicity to the fetus as well as the increasing rates of Multidrug-Resistant (MDR) strain isolation. A recent study by Edrees et al. documented the positive growth of bacteriuria among 18% urine specimens from pregnant women and the high frequency of bacteriuria (61.1%) among women with primary and second gravida. The bacterial isolates showed high susceptibility to antibiotics indicating that the resistance profile is required to determine the effective antibiotic before prescription for pregnant women. Proper investigation and prompt treatment are needed to prevent serious life-threatening conditions and morbidity due to UTI that can occur in pregnant women. There is a prerequisite for low-cost and accurate methods for UTI screening in pregnancy and efforts to address increasing rates of antibiotic resistance in developing countries.